PERSUASIVE & RHETORICAL IMPACT OF IDIOMS REFLECTING LIFE (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article explores the persuasive and rhetorical power of idioms that reflect aspects of life experiences, such as challenges, successes, relationships, and personal growth. It argues that these linguistic tools, deeply embedded in cultural understanding, effectively convey complex ideas, evoke empathy, and foster a sense of shared human experience. Through their evocative imagery and succinct expression, life-reflecting idioms not only add color to language but also serve as potent instruments for persuasion and rhetorical effect, influencing perception and shaping understanding.